2022
DOI: 10.3390/biomedicines10030557
|View full text |Cite
|
Sign up to set email alerts
|

Role of Base Excision Repair in Innate Immune Cells and Its Relevance for Cancer Therapy

Abstract: Innate immunity is critical for immediate recognition and elimination of invading pathogens or defense against cancer cell growth. Dysregulation of innate immune systems is associated with the pathogenesis of different types of inflammatory diseases, including cancer. In addition, the maintenance of innate immune cells’ genomic integrity is crucial for the survival of all organisms. Oxidative stress generated from innate immune cells may cause self-inflicted DNA base lesions as well as DNA damage on others nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…It was found that high-risk population was mainly enriched in base excision repair (BER), cell cycle, mismatch repair, and other pathways ( Figure 8(c) ), while the low-risk group was mainly enriched in drug metabolism-cytochrome P450, fatty acid degradation, primary bile acid biosynthesis, tryptophan and tyrosine metabolism, and other pathways ( Figure 8(d) ). Three representative genes (NEIL2, OGG1, and APEX1) of BER were upregulated in high-risk population [ 15 ], confirming that patients with a high risk had more enriched BER activity (Supplementary Figure S4(b) ).…”
Section: Resultsmentioning
confidence: 88%
“…It was found that high-risk population was mainly enriched in base excision repair (BER), cell cycle, mismatch repair, and other pathways ( Figure 8(c) ), while the low-risk group was mainly enriched in drug metabolism-cytochrome P450, fatty acid degradation, primary bile acid biosynthesis, tryptophan and tyrosine metabolism, and other pathways ( Figure 8(d) ). Three representative genes (NEIL2, OGG1, and APEX1) of BER were upregulated in high-risk population [ 15 ], confirming that patients with a high risk had more enriched BER activity (Supplementary Figure S4(b) ).…”
Section: Resultsmentioning
confidence: 88%
“…The BER pathway is primarily responsible for removing and repairing base lesions caused by oxidation, depurination, alkylation, and deamination, which help maintain the integrity of the genome under constant threat of environmental stresses (Stratigopoulou et al, 2020). Keeping genome integrity in immune cells is extremely important for their homeostasis, differentiation, and proliferation in response to internal and external stresses such as infection (Zhao et al, 2022). Except for its functions in DNA repair, BER pathway has been recently shown to regulate RNA metabolism and gene expression through transcriptional and post-transcriptional mechanisms (Antoniali et al, 2017), indicating this pathway may be a regulatory all-rounder.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen and nitrogen species produced by immune cells at sites of infection can induce DNA damage, and further amplify the inflammatory response. Dysfunctional DNA repair enzymes and dysregulation of DNA repair pathways can lead to the accumulation of DNA damage, and activation of innate immune signaling, suggesting a role for DNA repair proteins in the innate immune response (Kidane et al, 2014; Zhao et al, 2021; Zhao et al, 2022). NEIL2 is involved in the regulation of innate immunity via repair‐mediated regulation and repair‐independent regulation.…”
Section: Function Of Neil2mentioning
confidence: 99%